(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article shows ways to reduce the risk level of investment projects. These methods help reduce risk and make investment projects effective